Predictors for good knowledge regarding mercury hygiene among primary healthcare workers in Seremban, Negeri Sembilan - Mohd Zainee, Zaza Hulwanee; Muhamad Saliluddin, Suhainizam (Community Health Society Malaysia, 2017)
Background: Mercury poses a serious threat to human and environmental health. In Malaysia, health industry contributes to approximately 10% of mercury emissions and releases. Healthcare workers are potentially at risk for occupational mercury exposure, thus, should be equipped with proper training in mercury hygiene to ensure safety and health at work as well as to reduce the impact of mercury on the environment. This study was aimed to assess the level of and predictors for good knowledge regarding mercury hygiene among primary healthcare workers in Seremban, Negeri Sembilan. Materials and Methods: A cross-sectional study was conducted from April 2017 to June 2017 among 578 primary healthcare workers working in primary healthcare facilities in Seremban, Negeri Sembilan. Study subjects were selected using proportionate stratified random sampling method and handed a pre-tested and validated self-administered questionnaire. The data analysis was performed using SPSS version 22.0. Multiple logistic regression was used to identify predictors for good knowledge. Result: The response rate was 91%. The majority of respondents were health professionals (55.3%), worked in medical facilities (75.7%), and had less than 20 years of working experience (89.4%). Only 23.7% of the respondents had attended training in mercury hygiene, 15.4% had previous exposure to mercury spillage and 8.1% had prior experience in cleaning mercury spillage. Most of the respondents (81.2%) had good knowledge. Significant predictor for good knowledge was job - health professionals (AOR = 5.94, 95% CI [2.25, 15.66], p < 0.001) and health associate professionals (AOR = 2.61, 95% CI [1.36, 5.00], p = 0.004). Conclusion: The overall level of knowledge regarding mercury hygiene among primary healthcare workers in Seremban was satisfactory. Future education and training in mercury hygiene should target personal care workers in health service than other healthcare worker groups.